NuSTAR Spectral Analysis beyond 79 keV with Stray Light - Mastroserio, G.; Grefenstette, B. W.; Thalhammer, Philipp; Buisson, D. J. K.; Brumback, M. C.; Ludlam, R. M.; Connors, R. M. T.; Garcia, J. A.; Grinberg, Victoria; Madsen, K. K.; Miyasaka, H.; Tomsick, J. A.; et al. (Astrophysical Journal, 2022)
Due to the structure of the NuSTAR telescope, photons at a large off axis (>1 degrees) can reach the detectors directly (stray light), without passing through the instrument optics. At these off-axis angles NuSTAR essentially turns into a collimated instrument and the spectrum can extend to energies above the Pt K edge (79 keV) of the multilayers, which limits the effective area bandpass of the optics. We present the first scientific spectral analysis beyond 79 keV using a Cygnus X-1 observation in StrayCats: the catalog of stray light observations. This serendipitous stray light observation occurred simultaneously with an INTEGRAL observation. When the spectra are modeled together in the 30-120 keV energy band, we find that the NuSTAR stray light flux is well calibrated and constrained to be consistent with the INTEGRAL flux at the 90% confidence level. Furthermore, we explain how to treat the background of the stray light spectral analysis, which is especially important at high energies.
CRIS-Team WoS Importer:2023-02-03